Investigations on the field bio-efficacy of some newer insecticides against insect pests of brinjal (Solanum melongena L.) - Sunda, N. R.; Kumar, Ashok; Bajpai, N.K.; Mandarwal, Neelam (Annals of Agricultural Research, 2016)
A field trial was conducted to investigate the field bio efficacy of some newer insecticides against insect pests of brinjal at horticultural farm Rajasthan College of Agriculture, Udaipur during August-December 2008. Spirotetramat + imidacloprid @ 75 + 75 g a.i./ha was found most effective for the control of jassids and white flies as it accounted more than 76.11 per cent control, even after fourteen days of spraying. Imidacloprid 200 SL @ 75 g a.i./ha was found better than other treatments in reducing jassids and white flies population which was statistically at par with spirotetramat + imidacloprid @ 60 + 60 g a.i./ha. Spirotetramat 150 SC @ 75 g a.i./ha was adjudged most superior for the control of brinjal shoot and fruit borer. Dicofol and imidacloprid proved to be the least effective and flubendiamide gave moderate control of shoot and fruit borer which was at par with beta-cyfluthrin. Ready mixture of spirotetramat + imidacloprid and all the other insecticides did not show any photo toxic effect on brinjal plants.